The result of using blood-saving technologies when removing a giant meningioma of the wings of the sphenoid bone: a case report - A. V. Kuligin; A. Lushnikov; A. M. Fisun; A. G. Novikov; O. A. Balatsky; S. N. Shcherbakov; Yu. A. Smirnov; E. A. Lushnikova; N. A. Broyaka; E. E. Zeulina (Вестник анестезиологии и реаниматологии, 2024)
Neurosurgical operations to remove giant brain tumors, thanks to the development of high-tech operating techniques, are rarely accompanied by massive intraoperative blood loss (especially when removing tumors of glial origin). However, when removing meningiomas characterized by greater variability in location and blood supply, massive intraoperative blood loss may develop. Since May 2023, the State Healthcare Institution «Regional Clinical Hospital» in Saratov, within the framework of interdisciplinary cooperation of services – neuro- and x-ray surgery, anesthesiology-resuscitation and transfusiology, has begun the integrated use of blood-saving technologies in patients during operations to remove giant-brain tumors. The authors present the case of successful use of blood-saving technologies in the coordinated work of the above services to provide surgical treatment of the patient with a giant meningioma of the wings of the sphenoid bone on the left.